POLA PERSEBARAN PERMUKIMAN PENDUDUK DI KECAMATAN TALIABU BARAT LAUT KABUPATEN TALIABU - Adriansyah, Adriansyah; Musyawarah, Rahma (UNIVERSITAS NEGERI MAKASSAR, 2019)
The formulation of the problem in this study are: 1) What is the pattern of population settlements in Taliabu Barat Northwest District Taliabu District, 2) What are the factors that influence the population settlement patterns in Taliabu Northwest District Taliabu District. The purpose of this study is 1) To describe the population settlement patterns in Taliabu Northwest District, Taliabu Regency. 2) To find out the factors that influence the population settlement patterns in Taliabu Northwest District Taliabu District. This type of research is descriptive qualitative using a case study approach. Data collection techniques are observation, questionnaire, and documentation.Analysis of the pattern of settlement distribution was measured using the analysis of the nearest neighbor (nearest neighbor analysis), namely by calculating the size of the nearest neighbor parameter (T). Based on the results of the research on the Distribution Pattern of Population Settlements in Taliabu Northwest Subdistrict, Taliabu District, the pattern is uniform because the value of T â‰¥ 1.4 is the value of T = 2.54 m and patterned to follow the path or linear settlement pattern. Factors of settlement distribution patterns in Taliabu Northwest Subdistrict, Taliabu Regency are influenced by: First the community prefers to establish settlements in the coastal area of 67.3% and close to the road by 56.4%; The two of them mostly use their land as plantation land of 78.2% and agricultural land by 20%; The third source of water comes from the PDAM of 50.9% and is> 31 m at 54.5%; The four availability of natural resources mostly comes from agriculture / plantations, which is 96.4%.Â